'The Great Blow' and the Politics of Popular Royalism in Civil War Norwich. (28th February 2018) - Hopper, Andrew
Abstract: This article explores popular politics and royalism during the English Civil Wars through the reaction of magistrates to the riot in Norwich on 24 April 1648 that was referred to by contemporaries as the 'mutiny' or the 'Great Blow'. On the eve of the Second Civil War, this confrontation between urban rioters and New Model Army troopers led to the largest explosion of gunpowder in seventeenth-century England, when ninety-eight barrels were ignited at the Committee House. The article analyses the 278 witness statements that were produced as part of the judicial inquest, making this the best documented provincial riot of the early modern period. These previously neglected proceedings can do much to advance our understanding of popular politics, royalism and urban culture. Therefore the article focuses on how the rioters mobilised and generated crowds through petitioning, subscription, print, preaching, rumour, health-drinking, seditious words, and gestures. It assesses participants' social origins and places them within contrasting local religious and political cultures in a battle for control of the key public spaces of the city. The seditious words revealed in the testimonies cannot be dismissed as merely anti-parliamentarian, and in many cases illuminate how a politics of popular royalism was revived in the city. The episode highlights how both national and local, and elite and popular politics overlapped and were entwined by civil war.